Korelasi Manajemen Berbasis Sekolah Dan Pengelolaan Pembelajaran Pendidikan Agama Islam Terhadap Perilaku Akhlak Siswa (Studi Kasus di SMPN 23 Kota Tangerang) - Suhada Suhada; Verra Veronica; Mauidhotul Hasanah (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
Based on descriptive analysis obtained by school based management and management of learning PAI on moral behavior of students (school quality) in SMPN 23 Tangerang City mostly in good category. While the results of regulatory analysts show school management and management of learning PAI together provide a significant effect on moral behavior (quality of school). The implications of the research findings that found that school-based management variables and the quality of learning management of PAI have a significant influence on school quality (behavior of morality of students) in SMPN 23 Kota Tangerang, then in the implementation of SBM in all SMPN Kota Tangerang, headmaster. In addition, the guidance of PAI teachers as the organizer of learning in the classroom should be improved. The purpose of this research is to describe school management and management of PAI learning and school quality in SMPN 23 Kota Tangerang. The population of this study were 1427 respondents and samples of 100 people. This research data was collected by using questionnaires for all variables and documentation methods to collect secondary data. The questionnaire instrument has been tested and analyzed its validity and reliabelitias very well. Data analysis used is descriptive analysis by using criterion and relationship test by using regression analysis.